Interleukins as new prognostic genetic biomarkers in non-small cell lung cancer. (September 2017) - Pérez-Ramírez, Cristina; Cañadas-Garre, Marisa; Alnatsha, Ahmed; Molina, Miguel Ángel; Robles, Ana I.; Villar, Eduardo; Delgado, Juan Ramón; Faus-Dáder, María José; Calleja-Hernández, Miguel Ángel
Abstract: Background: Surgery is the standard treatment for early-stage NSCLC, and platinum-based chemotherapy remains as the treatment of choice for advanced-stage NSCLC patients with naïve EGFR status. However, overall 5-years relative survival rates are low. Interleukins (ILs) are crucial for processes associated with tumor development. In NSCLC, IL1B, IL6, IL12A, IL13 and IL16 gene polymorphisms may contribute to individual variation in terms of patient survival. The purpose of this study was to evaluate the association between IL gene polymorphisms and survival in NSCLC patients. Methods: A prospective cohorts study was performed, including 170 NSCLC patients (114 Stage IIIB-IV, 56 Stage I-IIIA). IL1B (C > T; rs1143634), IL1B (C > T; rs12621220), IL1B (C > G; rs1143623), IL1B (A > G; rs16944), IL1B (C > T; rs1143627), IL6 (C > G; rs1800795), IL12A (C > T; rs662959), IL13 (A > C; rs1881457) and IL16 (G > T; rs7170924) gene polymorphisms were analyzed by PCR Real-Time. Results: Patients with IL16 rs7170924-GG genotype were in higher risk of death (p = 0.0139; HR = 1.82; CI95% = 1.13–2.94) Furthermore, carriers of the TT genotype for IL12A rs662959 presented higher risk of progression in the non-resected NSCLC patient subgroup (p = 0.0412; HR = 4.49; CI95% = 1.06–18.99). The rest of polymorphisms showed no effect of on outcomes. Conclusions: Our results suggest that IL16 rs7170924-GG and IL12A rs662959-TT genotypes predict higher risk of death and progression, respectively, in NSCLC patients. No influence of IL1B rs12621220, IL1B rs1143623, IL1B rs16944, IL1B rs1143627, IL6 rs1800795, IL13 rs1881457 on NSCLC clinical outcomes was found in our patients. Highlights: ILs gene polymorphisms are associated with tumor development. NSCLC patients with IL16 rs7170924-GG genotype were in higher risk of death. Non-resected NSCLC patients with IL12A rs662959-TT genotype presented shorter PFS. The rest of polymorphisms showed no effect on platinum based outcomes.